Analisis Partisipasi Siswa SMA Dalam Mengakses Layanan Konseling Karir Berbasis Chatbot AI - Hery Wiharja; Evi Rahmiyati; Muhammad Ghifari Ilham; Maya Marselia (VOCATECH: Vocational Education and Technology Journal, 2026)
AbstractCareer guidance and counseling play a central role in assisting senior high school students in determining their educational and professional futures that align with their potential and interests. This study aims to analyze the participation of senior high school students in accessing AI chatbot-based career counseling services in two leading schools. The research method employed is Participatory Action Research (PAR) using a descriptive quantitative approach. The research sample consisted of grade X, XI, and XII students from SMAN Unggul Tunas Bangsa and SMAN Unggul Harapan Persada, totaling 220 respondents categorized by class, gender, and service access time. Data were collected based on the total number of users accessing career services through both face-to-face and AI chatbot modes. The findings revealed a significant increase in the number of accesses to AI chatbot-based career counseling services compared to face-to-face counseling across all grade levels. In terms of gender, female students tended to be more active and open in utilizing digital services, while male students preferred technology-based solutions offering greater privacy and flexibility. Moreover, most students preferred to access the services outside school hours, emphasizing the need for flexible, anytime-anywhere, accessible, and user-friendly platforms. The study concludes that AI chatbot-based career counseling effectively enhances participation, broadens access, and accommodates students’ diverse needs across grade levels, genders, and service times. The developed AI chatbot is expected to be adopted more extensively and adaptively by schools as a technology-based counseling service to better prepare students for the challenges of the digital-era workforce. AbstrakBimbingan dan konseling karir memegang peran sentral dalam membantu siswa Sekolah Menengah Atas (SMA) menentukan masa depan pendidikan atau profesi yang sesuai dengan potensi serta minat mereka. Penelitian ini bertujuan untuk menganalisis partisipasi siswa SMA dalam mengakses layanan konseling karir berbasis chatbot AI di dua sekolah unggulan. Metode penelitian yang digunakan adalah Participatory Action Research (PAR) dengan pendekatan kuantitatif deskriptif. Sampel penelitian terdiri atas siswa SMA kelas X, XI, dan XII pada SMAN Unggul Tunas Bangsa dan SMAN Unggul Harapan Persada, dengan total responden sebanyak 220 orang yang dibagi berdasarkan kelas, gender, dan waktu akses layanan. Data terhimpun dari jumlah total yang mengakses layanan karir secara tatap muka maupun melalui chatbot AI. Hasil penelitian menunjukkan terjadinya peningkatan signifikan jumlah akses layanan konseling karir berbasis chatbot AI dibandingkan dengan layanan tatap muka pada semua jenjang kelas. Secara gender siswa perempuan cenderung lebih aktif dan terbuka dalam memanfaatkan layanan digital, sedangkan siswa laki-laki lebih memilih solusi teknologi yang menawarkan privasi dan fleksibilitas. Selain itu, sebagian besar siswa lebih memilih mengakses layanan di luar jam belajar, menegaskan kebutuhan akan keleluasaan atas akses anytime-anywhere, accessible serta akses yang user-friendly. Kesimpulan penelitian ini adalah konseling karir berbasis chatbot AI efektif meningkatkan partisipasi, memperluas akses, dan mengakomodasi kebutuhan siswa lintas kelas, gender, serta waktu pelayanan. Chatbot AI hasil penelitian ini diharapkan dapat diadopsi sebagai layanan konseling berbasis teknologi oleh sekolah secara lebih intensif dan adaptif untuk mempersiapkan siswa menghadapi tantangan dunia kerja di era digital.